A hypermedia knowledge management system for conflict resolution and policy-making for new telecommunications services. (1st January 2000) - Temme, Jeroen Th.; Beroggi, Giampiero E.G.
All EU countries must establish a regulatory Commission for Networks and Services (CNS) whose main task is to resolve conflicts between competitors in a liberalised telecommunications market. A multimedia knowledge-management and advisory system has been developed for the Dutch CNS based on the problem-specific conceptual model of knowledge structure and on Holsapple's knowledge-oriented perspective of decision-making. The advisory system knows six user levels for knowledge acquisition, modification, and processing. The system has been developed together with CNS personnel. The system evolves along with its day-to-day use and it is expected to extend CNS' capability for knowledge management and to improve the quality of conflict resolution in interoperability conflicts.